The Influence of Organizational Commitment, Competence of Village Fund Management Offficers, and Utilization of Information Technology on Accountability of Village - Siska Apriana; Darwis Said; Nurleni Nurleni (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This study aims to analyze the effect of commitment of organization, competence of village fund management officers, and utilization of information technology on accaountability of village financial management either partially or simultaneously.The data used in the study are primary data in the form of questionnaires with a total sample of 96 respondents. The method used is a quantitative approach and multiple linear regression analysis which determined by purposive sampling method. The findings from this research indicate that (1) partially commitment of organization, competence of village fund management officers and utilization of information technology has a positive effect and significant impact on the accountability of village financial management (2) commitment of organization, competence of village fund management officers and utilization of information technology has simultaneous effect on the accountability of village financial management.